Ten nasty little toads - Cole, Stephen (Zephyr, 2019)
In these ten delightfully humorous tales of a decidedly blackish hue, ten follysome toads can never change their beastly habits despite the efforts of a goodly witch
Keywords: Toads / Juvenile fiction; Witches / Juvenile fiction; Conduct of life / Juvenile fiction; Children's stories; Conduct of life; Toads; Witches